Seismic behavior and damage assessment of two historical fortified masonry palaces with corner towers. (April 2022) - Valente, Marco
Abstract: Recent earthquakes have highlighted that historical fortified masonry constructions may suffer extensive damage, even under low-to-moderate seismic actions, and corner towers may be one of the most vulnerable structural elements. An accurate assessment of the structural seismic performance is one of the most effective tools to deeply understand and identify the main structural weaknesses of such a building typology. To this aim, the need to properly simulate the dynamic behavior of large complex masonry buildings can strongly limit the application of simplified analysis methods widely used in common practice and largely presented in the literature. The objective of this study is to provide a comprehensive numerical insight into the earthquake response and seismic vulnerability of historical fortified masonry palaces with corner towers using non-linear dynamic analyses and a macro-modelling FE-based approach, which is able to take into account the complex interactions between different macro-elements and the characteristics of the seismic action. After a knowledge phase of the geometrical and constructive features of the two palaces under study, detailed three-dimensional FE models have been developed and predictive non-linear dynamic analyses have been performed to assess damage patterns and identify the most critical macro-elements. The numerical analyses highlight that the seismic response and damage distributions are significantly influenced by the geometrical features and main dynamic properties of the two palaces. A fundamental role is also played by the interactions of the different macro-elements with the adjacent structural parts. The results of the non-linear dynamic analyses point out that the two palaces are highly vulnerable to seismic actions, highlighting the onset of possible local collapse mechanisms and recurrent damage concentrations. For both the palaces, the most critical elements are the corner towers that present remarkable cracks patterns along the height, in the connection regions with the adjacent walls, in the upper part and in the vaults. Widespread damage is also observed in the macro-elements that are characterized by high slenderness, large openings and small walls thickness, and in the large vaults of the two palaces. A clear correlation between large displacements and high values of energy density dissipated by tensile damage is generally observed for the main critical macro-elements of both the palaces. The main outcomes presented in this study may also represent a useful insight to improve the knowledge and better understand the earthquake response and seismic vulnerability of similar historical fortified masonry palaces located in the same region, providing valuable information for practical applications in seismic risk assessment and mitigation at territorial scale.